Computational methods for NMR and MS for structure elucidation II: Database resources and advanced methods - Valli, Marilia; Russo, Helena Mannochio [UNESP]; Pilon, Alan Cesar [UNESP]; Pinto, Meri Emili Ferreira [UNESP]; Dias, Nathalia B.; Freire, Rafael Teixeira; Castro-Gamboa, Ian [UNESP]; da Silva Bolzani, Vanderlan [UNESP] (De Gruyter, 2020)
Technological advances have contributed to the evolution of the natural product chemistry and drug discovery programs. Recently, computational methods for nuclear magnetic resonance (NMR) and mass spectrometry (MS) have speeded up and facilitated the process of structural elucidation even in high complex biological samples. In this chapter, the current computational tools related to NMR and MS databases and spectral similarity networks, as well as their applications on dereplication and determination of biological biomarkers, are addressed.
Keywords: Dereplication; NMR and MS databases; Spectral similarity networks